Frictional behaviour of trimethylolpropane (TMP) oleate atdifferent regimes of lubrication / A.F. Maarof ... [et al.] - Maarof, A.F; Hamdan, S.H; C.T., Lee; W.W.F., Chong (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
Trimethylolpropane (TMP) esters possess good frictional properties, portraying good potential as alternative bio-lubricants. However, the most common TMP ester, which is TMP oleate, is found to be widely used only for hydraulics application. Therefore, to explore its potential usage in automotive applications, the present study determines the frictional behaviour of TMP oleate at different operating lubrication regimes. Friction forces for TMP oleate lubricated conjunction, consisting of cast iron pin being rotated against a stainless-steel disk, are measured using a pin-on-disk type tribometer. The applied normal load is 3 kg while the disk rotational speed is varied between 20 rpm and 2000 rpm. Along fluid film and boundary lubrication regimes, the average coefficients of friction for TMP oleate lubricated conjunction are measured to be 0.074 and 0.101, respectively. Along fluid film lubrication regime, with the maximum Hertzian pressure being calculated to be 1.1 GPa, the contact is expected to be elastohydrodynamic in nature. Transitions of lubrication regimes, similar to the classical Stribeck curve, are also observed between sliding velocities of 1.8 m.s-1 and 2.7 m.s-1 . Hence, the measured Stribeck curve demonstrates the potential use of TMP oleate for automotive applications, where a large range of operating lubrication regimes is required.